A practical synthesis of three aliphatic metabolites of capsaicin: 16-Hydroxycapsaicin, 17-hydroxycapsaicin, and 16,17-dehydrocapsaicin - Li, Die; Guo, Lulu; Guo, Xiaodong; Mao, Jian; Liu, Fuqiang; Chai, Guobi; Shi, Qingzhao; Ji, Lingbo; Wang, Dingzhong; Zhang, Qidong; Fan, Wu (Synthetic communications, 2023)
The first straightforward synthesis of 16-hydroxycapsaicin, 17-hydroxycapsaicin and 16,17-dehydrocapsaicin, the major aliphatic metabolites of capsaicin, is reported. The amidation of hept-6-enoic acid with vanillylamine hydrochloride, followed by olefin metathesis using 2-methylbut-3-en-2-ol as partner furnished 16-hydroxycapsaicin in 56.1% overall yield with excellent E-selectivity. The E-selective olefin metathesis of methyl hept-6-enoate with but-3-en-2-one led to α,β-unsaturated ketone compound, which was subject to Wittig reaction with Ph 3 P + MeBr - , providing the corresponding 1,3-diene derivative. After removing methyl group by hydrolysis and introducing hydroxyl group by hydroboration-oxidation, such diene could be further converted to 16,17-dehydrocapsaicin and 17-hydroxycapsaicin with overall yields of 35.6 and 7.8%, respectively.